The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1097/psy.0000000000000348
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Multicomponent Life-Style Intervention on Weight, Glycemic Control, Depressive Symptoms, and Renal Function in Low-Income, Minority Patients With Type 2 Diabetes: Results of the Community Approach to Lifestyle Modification for Diabetes Randomized Controlled Trial

Abstract: Objective Few interventions have combined lifestyle and psychosocial approaches in the context of type 2 diabetes management. The purpose of this study was to determine the effect of a multi-component behavioral intervention on weight, glycemic control, renal function and depressive symptoms in a sample of overweight/obese adults with type 2 diabetes and marked depressive symptoms. Methods A sample of 111 adults with type 2 diabetes were randomly assigned to a 1-year intervention (n = 57) or usual care (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
80
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(83 citation statements)
references
References 40 publications
(43 reference statements)
1
80
1
1
Order By: Relevance
“…Depressive and anxiety symptoms were assessed in all but one study, which included a QoL outcome (Kuijer et al, 2007 ). Depressive symptoms were assessed using the Centre for Epidemiologic Studies Depression scale (CES-D) in two studies (Penckofer et al, 2012 ; Huang et al, 2015 ), the 9-item Patient Health Questionnaire (PHQ-9) in two studies (Rosland et al, 2015 ; Stoop et al, 2015 ), and the Beck Depression Inventory II (BDI) in one study (Moncrieft et al, 2016 ). Anxiety was measured in three studies and was assessed using the Crown-Crisp Experiential Index (CCEI) somatic anxiety subscale in one study (D'Eramo Melkus et al, 2010 ), the State Trait Anxiety Inventory (STAI) in one study (Penckofer et al, 2012 ) and the 7-item Generalized Anxiety Disorder questionnaire (GAD-7) in one study (Stoop et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Depressive and anxiety symptoms were assessed in all but one study, which included a QoL outcome (Kuijer et al, 2007 ). Depressive symptoms were assessed using the Centre for Epidemiologic Studies Depression scale (CES-D) in two studies (Penckofer et al, 2012 ; Huang et al, 2015 ), the 9-item Patient Health Questionnaire (PHQ-9) in two studies (Rosland et al, 2015 ; Stoop et al, 2015 ), and the Beck Depression Inventory II (BDI) in one study (Moncrieft et al, 2016 ). Anxiety was measured in three studies and was assessed using the Crown-Crisp Experiential Index (CCEI) somatic anxiety subscale in one study (D'Eramo Melkus et al, 2010 ), the State Trait Anxiety Inventory (STAI) in one study (Penckofer et al, 2012 ) and the 7-item Generalized Anxiety Disorder questionnaire (GAD-7) in one study (Stoop et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Self-management includes measuring and recording blood glucose, exercising, maintaining a diabetes diet, and regularly taking medication. Many studies have indicated that improvement in dietary and physical activity habits can prolong life expectancy in patients with T2DM [4, 5]. …”
Section: Introductionmentioning
confidence: 99%
“…The full-text versions of the remaining articles were reviewed for eligibility resulting in the exclusion of 224 for the reasons noted. Ultimately, 62 studies were included from the search, reporting on 60 unique patient samples 23 25–86…”
Section: Resultsmentioning
confidence: 99%